2015
DOI: 10.5815/ijmecs.2015.11.07
|View full text |Cite
|
Sign up to set email alerts
|

Facebook Applications to Promote Academic Engagement: Student’s Attitudes towards the Use of Facebook as a Learning Tool

Abstract: The aim of this study is to investigate highereducation student"s attitude toward the use of Facebook, as one of the social media tool, to enhance their education. This study was conducted on college students at one of the Jordanian higher educational institution. The number of participants of this study was forty five students who were enrolled in Computer Educational course. This course is either a graduation requirement for all elementary education major students or as an elective course for other student"s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…However the finding does provide a useful validation; given that the strengths and weaknesses of Blackboard and Facebook are complementary students actually do find using both to be an attractive proposition. However, even when students are lacking in computing and Facebook experience, such as in the study by AlMashaqbeh [30] the acceptance of such tools as support for learning is high.…”
Section: Discussionmentioning
confidence: 99%
“…However the finding does provide a useful validation; given that the strengths and weaknesses of Blackboard and Facebook are complementary students actually do find using both to be an attractive proposition. However, even when students are lacking in computing and Facebook experience, such as in the study by AlMashaqbeh [30] the acceptance of such tools as support for learning is high.…”
Section: Discussionmentioning
confidence: 99%
“…The assertions of Students C and D support studies that students feel motivated posting their accomplished tasks in the FB Group [27]. FB fostered their positive attitude in learning Research content and confidence.…”
Section: Motivationmentioning
confidence: 56%
“…FB is a useful tool to deliver course materials and support learning. Most respondents felt motivated and enjoyed accomplishing their tasks [27]. However, the students' excitement in the FB environment may lead to attention distraction, if not well-guided.…”
Section: B Impact Of Using Facebook In Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore it has been argued that Facebook may increase the sense of an academic 'community of practice' [13]. In a similar vein Facebook was positively received by students as a means of promoting community [14]. However not all of the findings suggest favourable outcomes from the adoption of Facebook, for example Dyson et al [15] found that it did not increase engagement in traditionally delivered fact to face lectures when it was adopted to support students in preparing for class.…”
Section: Introductionmentioning
confidence: 99%